Zinc, a very versatile chemical element - Piedra Marín, Gilberto (2019)
Zinc is a shiny metal whose surface quickly darkens upon contact with air. The main industrial application of this metal is the galvanization of iron and steel parts. Peru is the second largest producer of zinc worldwide, and regionally, the Ancash region is the first producer of this metal.